Unformatted text preview: d dx x x = d dx e x ln x = ± d dx x ln x ¶ e x ln x = ( x 1 x + ln x ) x x = (1 + ln x ) x x EXAMPLE 4.8 Recall that we have not justiﬁed the power rule except when the exponent is a positive or negative integer. We can use the exponential function to take care of other exponents. d dx x r = d dx e r ln x = ± d dx r ln x ¶ e r ln x = ( r 1 x ) x r = rx r1...
View
Full Document
 Fall '07
 JonathanRogawski
 Math, Calculus, Exponential Function, Derivative, Logarithmic Functions, Exponentiation

Click to edit the document details